Debunking the Myth of Pregnancy Doping - Elizabeth A. Sorensen (University of Kansas Libraries, 2009)
The notion that pregnancy and abortion are forms of doping has persisted for 20 years. Popular and scientific literature on pregnancy/abortion doping was critically analyzed to compare pregnancy/abortion doping with definitions of doping and blood doping and to compare pregnancy/abortion doping themes to current scientific knowledge. Main themes included oxygenation advantage and hormonal advantage. During pregnancy, maximal oxygen uptake may improve but not exercise performance. Human chorionic gonadotropin, the only pregnancy hormone on National Collegiate Athletic Association and United States Anti-Doping Agency banned substances lists, increases during pregnancy but there is no evidence that hCG enhances athletic performance in women. Recommendations include revising USADA and NNCAA policies into congruence with World Anti-Doping Agency policies which ban hCG for men only. During the past seven years of advocating for college student-athlete athletic department pregnancy and parenting policies, popular nonscientific literature (websites, blogs, and personal anecdotes) and scientific literature have been examined to detect barriers to student-athlete health and policy change. One barrier is a persistent belief in popular literature that athletes can use pregnancy and/or abortion to enhance competitive performance; i.e., as a form of prohibited blood doping. The scientific and nonscientific resources on pregnancy and abortion doping have considerably diverged over the past 20 years. The purposes of this paper were to examine the biophysical themes in popular and scientific definitions of doping, blood doping, and pregnancy /abortion doping, compare pregnancy/abortion doping to current scientific knowledge, and make recommendations to the stakeholders: student-athletes, coaches, athletic trainers, team physicians, athletic and university administrators, university faculty, the United States Anti-Doping Agency (USADA) and the National Collegiate Athletic Association (NCAA).